Analysis of occupational corruption in the light of sociological theories A theoretical analysis - فرج, نجاة محمد; حسێن, توانا فەرەیدون (Sulaimani Journal for Humanities, 2025)
Corruption in public office is a social phenomenon where an employee, while performing their official professional duties and responsibilities, exploits their position to achieve personal gains and benefits, or to benefit close associates, resulting in violations of laws and administrative regulations. Among the various social theories, there are those that address topics related to (systems, structures, functionality, roles, status, job confusion, and social relations), among others, within a range of social schools of thought. This research has benefited from these theories because they are relevant to its objectives, namely, analyzing the phenomenon of job corruption from the perspective of social theories. This research attempted to conduct a theoretical analysis of the phenomenon of functional corruption by utilizing and interpreting social theories in order to understand the phenomenon of functional corruption, its formation, and its emergence. The research relied on the structural functionalism school, symbolic interactionism, and role theory. These theories serve the theoretical objectives of the research and enable us to conduct a precise analysis of the phenomenon in question.